Chiral amino-acid-amide based ionic liquids as a stereoselective organocatalyst in asymmetric transfer hydrogenation of acetophenone at room-temperature - Javle, Balasaheb R.; Kinage, Anil K. (Chemistryselect, 2018)
Chiral Ionic Liquids (CILs) of amino acid amide were synthesized and used as novel organo catalyst for Asymmetric Transfer Hydrogenation (ATH) of acetophenone at room temperature. The developed CILs show very high yield and excellent enantio-selectivity in transfer hydrogenation of acetophenone.

Amino acid amide based ionic liquid as an efficient organo-catalyst for solvent-free knoevenagel condensation at room temperature - Burate, Pralhad A.; Javle, Balasaheb R.; Desale, Pranjal H.; Kinage, Anil K. (Catalysis Letters, 2019)
Ionic liquids of amino acid amide were synthesized and used as an efficient catalyst for solvent-free Knoevenagel condensation. Synthesized ionic liquids are an environmentally benign, inexpensive, metal free and plays the dual role of solvent as well as an efficient catalyst for Knoevenagel condensation. A wide range of aliphatic, aromatic and heteroaromatic aldehydes easily undergo condensation with malononitrile and ethyl cyanoacetate. The reaction proceeds at room temperature without using any organic solvent and is very fast with good to excellent yield. Additionally, the catalyst is easily separable and recyclable without loss of activity. [GRAPHICS] .
Keywords: Acrylonitrile; Amino acid amide; Cyanoacrylate; Ionic liquid; Knoevenagel condensation; Solvent-free